Improving dimensional and surface quality of additive manufactured parts. (April 2020) - Bruni, C; Gianangeli, C; Mancia, T; Greco, L; Pieralisi, M
Abstract: In modern manufacturing of polymer components the injection moulding represents the conventional way to get the desired shape respecting dimensional and surface requirements. But, such process plan requires the design of the tools and that of whole manufacturing process. A different choice could be done when the production consists of small batches or a single unit. In this case it is useful to realize the workpiece without tools taking into consideration the additive manufacturing technique. The limit of such flexible manufacturing technology is represented sometimes, in particular in working polymers such as ABS, by the difficulty to respect dimensional and surface requirements. The research activity to be presented involved the realization of cubic geometries in ABS by FDM (Fused Deposition Modeling). The staircase, the waviness and roughness of the surfaces were evaluated and quantified. The slight machining phase performed by front milling considered in the process plan allowed to reduce the staircase effect up to about zero and to reduce the waviness of about some decimals of millimeter to some hundredth of millimeter. The surface roughness was also improved. The methodology and the details are reported.